Penanaman Nilai-Nilai Islam dalam Upaya Pembentukan Karakter Melalui Pendidikan Agama Islam - Riska Rahmasari; Riski Rahmasari; Farhah Desrianty Gimri; Annisa Fitri Dewianti; Wismanto Wismanto (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This writing will discus the role of islamic religious education in schools in shaping students’personalities. PAI’s islamic religious education is one of the important pillars in character education. Character education will develop well if it it starts with instilling a religious spirit in children. Therefore PAI material in schools is a means of character education. Through studying PAI, students learn akidah as the basis of their religion, the Holy Qur’an and hadist as a guide to life, fiqh as a legal guide to worship, islamic history as a guide to life and examples, moral as a guide to human behavior, both good and bad. Therefore the main aim of PAI learning is to shape students’personalities which are realized through their behavior and thoughts in everyday life. Apart from that, PAI’s academic success at school is also determined by the application of appropriate learning methods.